PUBLIC RELATIONS MANAGEMENT IN INCREASING THE NUMBER OF STUDENTS AT SCHOOL - Hakim, Lukman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out: 1) To understand the Ahlussunnah Wal Jama'ah values-based curriculum planning management in Madrasas, 2) To understand the management of curriculum implementation based on Ahlussunnah Wal Jama'ah values in Madrasas, 3) To understand evaluation management Ahlussunnah Wal Jama'ah values-based curriculum in Madrasahs. This research uses descriptive qualitative analysis.